1999
DOI: 10.1034/j.1399-0004.1999.550110.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐inactivation and marker studies in three families with incontinentia pigmenti: implications for counselling and gene localisation

Abstract: Familial incontinentia pigmenti (IP) is an X-linked dominant disorder with an extremely variable clinical presentation. Ambiguous diagnosis can complicate genetic counselling and attempts to refine the gene location in Xq28. Marked skewing of X-inactivation patterns is a hallmark of IP and provides a means for investigating uncertain cases. We have conducted X-inactivation studies in three families where Xq28 marker studies were at odds with the original clinical assessment. The results indicate that no recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Hence, the female can present with the full blown phenotype that is also seen in males carrying a mutation in that gene [Frints et al., ; Hagens et al., ]. Second, cells with the mutation are only viable in case of extreme (but not complete) secondary skewing against this mutation with the prime example of incontinentia pigmenti (MIM# 308300) [Woffendin et al., ]. Third, a mutation causing ID can be accompanied by skewing that had occurred by chance.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the female can present with the full blown phenotype that is also seen in males carrying a mutation in that gene [Frints et al., ; Hagens et al., ]. Second, cells with the mutation are only viable in case of extreme (but not complete) secondary skewing against this mutation with the prime example of incontinentia pigmenti (MIM# 308300) [Woffendin et al., ]. Third, a mutation causing ID can be accompanied by skewing that had occurred by chance.…”
Section: Discussionmentioning
confidence: 99%
“…gether with the skin-pigmentation abnormality, constitute the typical IP phenotype. The IP gene is thought to be essential for viability, since affected hemizygous male individuals die in utero and female patients survive with the mutant X chromosome selectively inactivated (Parrish et al 1996;Woffendin et al 1999). On the basis of these characteristics, we screened a gene called "NEMO" and identified mutations in multiple IP patients (International IP Consortium 2000).…”
mentioning
confidence: 99%
“…Since IP is an X‐linked dominant disorder, it affects predominately females. Genetic analysis has indicated Xq28 to be the major locus for familial IP (4). It has recently been shown that most cases of IP are due to mutations in the gene for NEMO (NF‐kappaB essential modulator)/IKKgamma (IkappaB kinase‐gamma).…”
Section: Discussionmentioning
confidence: 99%